2022
DOI: 10.3390/s22208019
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pallet Detection Method for Automated Guided Vehicles Based on Point Cloud Data

Abstract: Automated guided vehicles are widely used in warehousing environments for automated pallet handling, which is one of the fundamental parts to construct intelligent logistics systems. Pallet detection is a critical technology for automated guided vehicles, which directly affects production efficiency. A novel pallet detection method for automated guided vehicles based on point cloud data is proposed, which consists of five modules including point cloud preprocessing, key point extraction, feature description, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The detailed steps are as follows: Set the range of point cloud neighborhood search radius r j from lower limit r min to upper limit r max with radius interval r d . The upper and lower limits of the radius range are determined by the average point cloud distance d p , which is defined as follows [ 32 ]: where N represents the total number of points in the pallet point cloud, and d m represents the distance of each key point q k from its nearest point. Set , , , where .…”
Section: The Proposed Pallet Pose Estimation Methodsmentioning
confidence: 99%
“…The detailed steps are as follows: Set the range of point cloud neighborhood search radius r j from lower limit r min to upper limit r max with radius interval r d . The upper and lower limits of the radius range are determined by the average point cloud distance d p , which is defined as follows [ 32 ]: where N represents the total number of points in the pallet point cloud, and d m represents the distance of each key point q k from its nearest point. Set , , , where .…”
Section: The Proposed Pallet Pose Estimation Methodsmentioning
confidence: 99%
“…Point cloud classification has been active in the research fields such as photogrammetry and remote sensing for decades. It has become an important part of intelligent vehicles [1], automatic driving [2], 3D reconstruction [3], forest monitoring [4], robot perception [5], traffic signage extraction [6] and so on. Due to factors like irregularity and disorder, high sensor noise, complex scenes and non-homogeneous density, point cloud classification is still challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Shao et al used an RGB-D camera to detect euro pallet objects, performing pallet detection from point cloud data. They proposed a new method by combining color and geometric shape data [13]. Upon reviewing the literature, it is observed that mobile robots are being increasingly employed for in-factory transportation and are still under development.…”
Section: Introductionmentioning
confidence: 99%